Analisis literatur isu pelantikan hakim syarie wanita di Malaysia - Nasohah, Zaini; Majemi, Fatimah; Mohd Kusrin, Zuliza; Muhammad Husni, Ahmad; Samurie, Mohd Al-Adib (UTM Press, 2016)
Qadi or judge is a significant post in a state. Islam has enumerated certain detailed and strict conditions for a person to be appointed as a judge. Among the conditions is appointing a male judge for the post. Discussion on this issue in Malaysia is still ongoing as there are states that have not giving opportunity for women to have the post. This article aims to analyze literature review on the issue in Malaysia. A comparative content analysis approach was applied in analyzing the data gathered. The analysis discovers that there are lot of writings in fiqh references that disagree with the appointment of female judges. However, contemporary writings show that a lot of writing that supported and agreed with the appointment of female judges in certain area of judgements.